2020
DOI: 10.1002/tox.22990
|View full text |Cite
|
Sign up to set email alerts
|

Isatidis Folium alleviates acetaminophen‐induced liver injury in mice by enhancing the endogenous antioxidant system

Abstract: Isatidis Folium (IF) has been clinically combined with acetaminophen (APAP), but the rationality of combinational therapy is still ambiguous. In the present study, the protective effect and related mechanism of IF on APAP-induced hepatotoxicity were evaluated. Hepatic histopathology and blood biochemistry investigations clearly demonstrated that IF could restore APAP-induced hepatotoxicity. Liver distribution study indicated that the hepatoprotective effect of IF on APAP is attributed to the reduction of N-ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Globally, acute APAP overdose is considered a major cause of drug‐induced hepatotoxicity and acute hepatic failure; however, the underlying pathophysiology remains poorly understood. The advantages of natural products, such as fewer side effects, low cytotoxicity, and substantial changes in bioactivity, have drawn considerable attention 22–24 . As one of the main active components of citrus fruits, naringin possesses several pharmacological effects, including antioxidant, antiinflammatory, and antiapoptotic properties 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, acute APAP overdose is considered a major cause of drug‐induced hepatotoxicity and acute hepatic failure; however, the underlying pathophysiology remains poorly understood. The advantages of natural products, such as fewer side effects, low cytotoxicity, and substantial changes in bioactivity, have drawn considerable attention 22–24 . As one of the main active components of citrus fruits, naringin possesses several pharmacological effects, including antioxidant, antiinflammatory, and antiapoptotic properties 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…natural products, such as fewer side effects, low cytotoxicity, and substantial changes in bioactivity, have drawn considerable attention. [22][23][24] As one of the main active components of citrus fruits, naringin possesses several pharmacological effects, including antioxidant, antiinflammatory, and antiapoptotic properties. 25,26 Previous studies have shown that naringin can exert hepatoprotective effects.…”
Section: Naringin Increases Hepatic Nrf2 Expressionmentioning
confidence: 99%
“…Paracetamol (acetaminophen) is a commonly used drug in clinic, which is mainly used for cold-induced fever, headache, joint pain, neuralgia, migraine, dysmenorrhea, and so on. Lycium Barbarum extract can significantly improve paracetamol-induced apoptosis to protect the liver from chemical damage ( Gündüz et al, 2015 ), and Isatidis Folium can enhance the endogenous antioxidant system and reduce paracetamol-induced liver damage in mice ( Ding and Zhu, 2020 ). Ahmed et al also found that Panax ginseng could be used as a hepatoprotective agent, which prevented cyclophosphamide (with immunosuppressive and anti-cancer potential)-induced liver injury by reducing the expression of TNF-α, IL-1β and Caspase3 genes, as well as increasing the BCL-2 gene expression, and its liver-protective effect is better than vitamin E ( Abdelfattah-Hassan et al, 2019 ).…”
Section: Characteristics Of Several Important Liver Diseasesmentioning
confidence: 99%
“…Folium Isatidis is an Isatis indigotica Fort (Chen et al, 2022; Ding & Zhu, 2020). It belongs to Isatis of Cruciferae.…”
Section: Introductionmentioning
confidence: 99%